FINANCING FOR SELF-HELP HOUSING IMPROVEMENT OF LOW-INCOME COMMUNITY (CASE STUDY: KAMPUNG AROUND INDUSTRIAL AREA BERBEK, WARU, SIDOARJO, INDONESIA). - Dana Wahyu Prismawan , Happy Ratna Santosa, Rika Kisnarini, Dewi Septanti (International Journal of Research Science and Management, 2018)
The condition of low-income community in provision of houses for themselves is still less feasible that related to inadequate economic condition. House is one of the basic human rights that must be obtained by the community. In Indonesia there are government programs that are intended for community housing, but more focused on the housing that was built formally, rather than self-help housing which built by the community, especially for lowincome community. Furthermore, some subsidized assistance policies are available for low-income community, but some requirements of procedure in obtaining it are potentially difficult, so that result in them not reaching this subsidy. This research aims to determine the form of provision of assistance in order to support the financing for self-help housing in accordance with the conditions of the low-income community with case studies on kampung (informal housing or village inner city) around the industrial area by descriptive field research method. The result of the research shows that there are potentials and problems in financing of self-help housing on lowincome community. Some strategies that can be done include maximize and equitable government programs on self-help housing finance for low-income community, increase the income of low-income community, and implement Corporate Social Responsibility.